Study of novel swirler design on the performances of non-premixed combustion - ABU MANSOR, KHALIL FIRDAUS; Abd Rashid, Razlin; Samiran, Nor Afzanizam (Progress in Engineering Application and Technology, 2021)
Combustion industries in recent decades has a problem to reduce the emissions with a good performance of combustion. This research aims to reduce emissions and also to increase velocity and temperature by using non premixed combustion. Axial swirler and radial swirler are combined in one design with each swirler having 8 blades. Swirl angle for radial swirler is 35° and inclination angle for axial swirler is 15°. The swirler is designed using Solidworks and transferred into a ANSYS fluent for the simulation and to get the results. The fuel used is LPG gas and turbulence parameters for this study is standard k-epsilon model. 3 line have been created on the simulation to get the result at different stages. The result proved that the combination swirler can reduce the CO and CO2 emission and also able to improve the velocity. The temperature result for axial swirler is better than combination swirler. As a recommendation, the axial part in the combination swirler need to increase their inclination angle to increase the temperature.